Oral lymphangioma: A rare case report - Harsha Bhayya; D Pavani; M L Avinash Tejasvi; P Geetha (Wolters Kluwer Medknow Publications, 2015)
Lymphangiomas are benign hamartomatous tumors of the lymphatic channels which present as developmental malformations arising from sequestration of lymphatic tissue that do not communicate with the rest of the lymphatic channels. Lymphatic vessels are filled with a clear protein-rich fluid containing few lymph cells. It can also occur in association with hemangioma. The onset of lymphangiomas are either at birth (60% to 70%) or up to two years of age (90%) and rare in adults. Lymphangiomas have marked predilection for the head and neck region (50-70%). The most common location in the mouth is the dorsum of tongue, followed by lips, buccal mucosa, soft palate, and floor of the mouth. On tongue, they may present as a localized or a diffused growth which may enlarge to cause macroglossia, impaired speech and difficulty in mastication. Herewith, we present a rare case of lymphangioma of tongue leading to macroglossia in a 8-year-old boy.